Effects of Different Bridges of A Series of c-Donor-nc-Bridge-cf- Acceptor Type Block Copolymers for Potential Solar Cell Applications - Hasib, Muhammad A.; Sun, Sam-Shajing (Journal of Research Updates in Polymer Science, 2019)
A series of c-D-nc-B-cf-A (or DBpfA, p=0,1,2,4,6) type of block copolymers has been designed, synthesized, and systematically studied for photo induced charge separations; where c-D is an electron-donating conjugated block, nc-B is a non-conjugated bridge unit, and cf-A is an electron-accepting conjugated and fluorinated block. A series of photoluminescence quenching measurements with and without different bridge units were evaluated for DBpfA. This study highlights the chemical molecular bridge effects on the optoelectronic property of the DBpfA type block copolymer. Specifically, the DB1fA block copolymer (where only one methylene unit is present in the bridge unit) appears exhibiting the best optoelectronic performance. DfA block copolymer (without any bridge unit) exhibits photoluminescence quenching and optoelectronic property that is between the shortest and longest bridge units, and this can be explained by the calculated four stable state twisting angles (most stable state is at a seventeen degree twist) between conjugated donor and conjugated acceptor blocks. The optoelectronic properties appear following the PL quenching nicely.